Hyperbole in song lyrics of sempiternal album by bring me the horizon - Sari, Putu Indira Cika Mantika; Santika, I Dw Ayu Devi Maharani; Juniartha, I Wayan (Journal of Language and Applied Linguistics, 2022)
This research aims to identify and to analyze the meaning of hyperbole applied in the song lyrics of Sempiternal album by Bring Me the Horizon. The data were collected from eleven songs within the album. The research applied descriptive qualitative analysis using theory of figurative language by Knickerbocker and Renninger (1963) to determine the lyrics that contain hyperbole and theory of meaning by Leech (1981) to analyze the meaning of the hyperbole. The data in this study were presented descriptively. The result of the analysis shows thirteen hyperboles are found in the lyrics. The meanings found based on the lyrics with hyperbole consist of three kinds, namely connotative, affective, and conceptual. The dominant meaning is connotative as the hyperbole cannot be interpreted lexically.